Assessment of Bleeding for the Evaluation of Therapeutic Preparations in Small Animal Models of Antibody-Induced Hemophilia and von Willebrand Disease - Turecek, P L; Gritsch, H; Richter, G; Auer, W; Pichler, L; Schwarz, H P (Thrombosis and Haemostasis, 1997)
Three small animal models of bleeding are described and used to evaluate the effects of preparations intended for therapy of human bleeding disorders. We modified techniques for the assessment of bleeding to be able to reproducibly quantify blood loss and rate of blood flow in addition to the measurement of bleeding time.Temporary hemophilia was induced in a rabbit model by injection of high titer human inhibitor plasma [>1000 Bethesda units (BU)/ml]. A decrease in rabbit FVIII from normal values to below the limit of detection was observed within 30 min, cuticle bleeding time changed from normal (approx. 10 min) to steady state bleeding (>30 min), and the rate of blood flow increased from 4 to >30 µl blood/min. Infusion of an activated prothrombin complex concentrate (FEIBA STIM4, Immuno) at doses between 75 and 150 U/kg normalized the rate of blood flow, while infusion of FVIII/vWF concentrate resulted in partial correction. Administration of FVIIa, both recombinant and plasma-derived, failed to correct bleeding, however. In an analogous murine model, FVIII/ vWF inhibitor plasma was obtained by immunizing goats with a purified human FVIII/vWF complex. This plasma cross-reacted with mouse vWF in vitro. Injection of the anti-FVIII/vWF inhibitor plasma into mice caused a decrease in vWF antigen, in some animals with a complete loss of vWF multimers comparable to severe von Willebrand disease. A specific anti-vWF inhibitor plasma obtained by immunization of goats with recombinant vWF was used in a further murine model, resulting in a gradual but substantial decrease in FVIII as well as in intensive bleeding. The infusion of a FVIII/vWF concentrate (IMMUNATE, IMMUNO) normalized the rate of blood flow in both murine models. The same assessment methods were used to characterize bleeding in a natural mouse model of von Willebrand disease (strain RIIIS/J). The use of quantitative techniques of assessment of blood loss and rate of blood flow appears to be a helpful tool for characterizing hemorrhagic situations and evaluating the capacity of therapeutic preparations to correct hemostatic defects.